Kyai-Santri Relationship in Electoral Politics : A Critical Point of View - Masruri Mahali; Wawan Sobari; George Towar Ikbal Tawwakal (Universitas Pancasakti Tegal, 2019)
This qualitative case study aims to explore the electoral political relations of the kiai and santri in the local leaders election of East Java.The kiai's authority is absolute, the submission of the santri to the kiai is the main rule of the pesantren culture, the relationship of the kiai and santri is patron-client, there is an unequal interaction with the position of the santri being a client and the kiai becoming a patron.The strength factor of the charisma and influence of the kiai is often used for various interests in the politics of regional elections. Different from theory, the patron-client relationship in the electoral political relations of the kiai and santri in the local leaders election of East Java is not relevant. This study finds, First, the electoral political relations of the kiai and santri are determined by the attitude of equal egalitarian relations and complementary relations. Kiai and santri both play a role in shaping voting behavior, and the kiai is no longer the dominant figure in determining santri's political choices, because there is a practice of political deliberation. Secondly, there are three typologies of electoral political relations between kiai and santri, namely, (1) Political relations are equal (associative), (2) Positive opposition political relations (dissociative-positive), and (3) Political relations mabadi ’khaira ummah ((prioritizing the interests of the ummah). Lastly, this case study of the electoral political relations of the kiai and santri adds new knowledge that the santri's political choices in regional elections are no longer based on patron-client relations.